Interaksi Tingkah Laku Ikan Cupang Jantan dan Betina (Betta Splendes) Pada Masa Kawin - Nugroho, Anwari Adi; Latifa, Ulin Nuha; Rahayu, Nova Yanti; Setyawan, Arif Fajar (Science Education and Application Journal, 2020)
This study aims to determine patterns of interaction of male and female betta fish behavior during mating. This research is an exploratory descriptive study in which observing the behavior of male and female betta fish periodically for three days in the morning and evening in aquariums that were given a barrier for an hour then unites male and female betta fish in one container and observe interactions between males and females for two hours in the afternoon. This research uses ad libitum sampling method, namely research by observing all activities that were seen based on field facts. The equipment used in the form of insulated glass aquariums and fishing nets, the material needed was a betta fish type as much as 6 tails. Data was collected by means of observation using observation sheets, observation notes, and documentation tools. The data collected was analyzed using descriptive analysis techniques that describe the behaviors that arise during observation. The results of observations in different containers showed that the behavior of the male betta fish was the most dominant make bubbles while the behavior of the female betta fish was the most dominant silence at the bottom of the aquarium. In one container, the most dominant male betta fish behavior was swim around the aquarium while the most dominant female betta fish behavior was to stay at the bottom of the aquarium.